1959
DOI: 10.1139/y59-061
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol and Plasma Cholesterol Levels in Man

Abstract: Sixty-three men and twenty women (university students) consumed a fat-free, homogeneous liquid formula ration for 8 days. Groups of 8 to 11 individuals were then transferred to diets in which 30% of the calories were supplied in the form of butter oil fractions which were substituted equicalorically for carbohydrate. The most volatile fraction, which was high in cholesterol (3.83%), caused a great increase in plasma cholesterol. The cholesterol-poor fractions led to relatively small increases but when suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1961
1961
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This possibility was investigated by incorporating into a compounded diet at a level to supply 30% of the calories a fraction of completely saturated coconut-oil triglycerides containing fatty acids of chain length C,-C,,. Despite the absence of double bonds, this fat did not cause an increase in plasma cholesterol level when added to a fat-free diet; even when cholesterol was added, no increase in plasma sterol levels occurred (Beveridge et al 1959). Similar findings were subsequently reported by Hashim, Arteaga & Van Itallie (1960) and by Grande, Anderson & Keys (1961).…”
supporting
confidence: 83%
See 4 more Smart Citations
“…This possibility was investigated by incorporating into a compounded diet at a level to supply 30% of the calories a fraction of completely saturated coconut-oil triglycerides containing fatty acids of chain length C,-C,,. Despite the absence of double bonds, this fat did not cause an increase in plasma cholesterol level when added to a fat-free diet; even when cholesterol was added, no increase in plasma sterol levels occurred (Beveridge et al 1959). Similar findings were subsequently reported by Hashim, Arteaga & Van Itallie (1960) and by Grande, Anderson & Keys (1961).…”
supporting
confidence: 83%
“…There is no doubt that the nature of the triglycerides and the constituent fatty acids of fats are in part responsible for their effects on plasma cholesterol level, but our work and that of Gordon, Wilkens & Brock (1958) demonstrate that degree of unsaturation is not the sole determinant and that certain other factors including the non-glyceride components also play a part. In experiments performed during the academic session of 1955-6 we obtained evidence that a hypercholesterolaemic factor in butter and a hypocholesterolaeniic factor in maize oil could be concentrated in the relatively volatile fractions obtained by molecular distillation of these fats (Beveridge, Connell & Mayer, 1957). Further work revealed that the cholesterol-rich distillate of butter was the most hypercholesterolaemic and that this was due at least in part to its content of cholesterol (Beveridge, Connell, Haust & Mayer, 1959).…”
Section: Symposium Proceedings I964mentioning
confidence: 94%
See 3 more Smart Citations